1977
DOI: 10.1007/bf01670278
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of anxiety and related symptoms with cerebrospinal fluid 5-hydroxyindoleacetic acid in depressed women

Abstract: Cerebrospinal fluid 5-hydroxyindoleacetic acid levels were determined in 31 women with unipolar involutional depression using the probenecid technique. Values were found to be lower in depression as compared to controls, but they did not correlate with the severity of the clinical picture. Anxiety, insomnia and drug response however showed significant correlation with pretreatment 5-HIAA level. Some possible interpretations are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…As revealed by the multiple regression analysis, melancholic features provide a significant contribution to 5-HT2 receptor responsiveness measure that is distinct and independent of irritability. Some studies have shown an inverse relationship between CSF 5-HIAA and anxiety in major depression (41,42,52). Several studies reported increased brain or platelet 5-HT2 receptors in patients with recent suicide attempts or with a lifetime history of suicidal behaviour (3-6, 50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As revealed by the multiple regression analysis, melancholic features provide a significant contribution to 5-HT2 receptor responsiveness measure that is distinct and independent of irritability. Some studies have shown an inverse relationship between CSF 5-HIAA and anxiety in major depression (41,42,52). Several studies reported increased brain or platelet 5-HT2 receptors in patients with recent suicide attempts or with a lifetime history of suicidal behaviour (3-6, 50).…”
Section: Discussionmentioning
confidence: 99%
“…However, Meltzer et al (33) function to history of suicide attempt rather than to suicidal ideation. Some studies have shown an inverse relationship between CSF 5-HIAA and anxiety in major depression (41,42,52). A post-synaptic 5-HT receptor system hypersensitivity hypothesis of anxiety has also been proposed that suggests that some anxiety states, and in particular panic disorder, are characterized by hypersensitive post-synaptic 5-HT receptors (18).…”
Section: Discussionmentioning
confidence: 99%
“…Lower levels of 5-hydroxyindoleacetic acid (5-HIAA), the major metabolite of 5-HT, in cerebrospinal fluid (CSF), have been found in both depressed and nondepressed patients who made violent suicide attempts compared to those whot did not (Asberg etal., 1976;Agren, 1980;van Praag, 1983;Banki and Arato, 1983). Reduced CSF 5-HIAA levels has also been found to be associated with high level of aggressive behavior towards self and others (Asberg etal., 1980(Asberg etal., , 1987, personality disorders with impulsive violent behavior (Brown et al, 1979) and high levels of anxiety and agitation in depressed patients (Banki, 1977;Asberg et al, 1980;Leckman etal., 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Such sepa rate analysis of distinct psychopathological symptoms as functions of bio chemical disorders has been already suggested by van Praag [32] and Zarifian and Loo [39]; by the use of explicit operational criteria for symp tom definition concordance can easily exceed 0.50 (intraclass correlation coefficient) and thus they serve as a solid base in the search for neurochem ical correlations. In fact, agitation and dopamine metabolism have been found to be interrelated in patients with depression, parkinsonism and other conditions independent of the diagnosis [30], There arc indications that a similar relationship may exist between the symptom cluster insom nia-agitation-anxiety and serotonin metabolism [9,19]. In the present study, CSF 5HIAA correlated positively with both hallucinations and dis orientation but not with agitation; this argues against the view that its CSF increase was only a consequence of a reduced egress or of motor hyperac tivity.…”
Section: Discussionmentioning
confidence: 99%